Development of viral vectors for passive immunisation against influenza - Tan, TK (2017)
Seasonal influenza is a major global health threat causing more than 500,000 deaths annually. Pandemic influenza can arise through antigenic shift, or when novel influenza strains escape from animal reservoirs, and can affect a large geographical area leading to a large number of deaths. Neither prior infection, nor current vaccines, provide lasting protection due to the rapid antigenic evolution of influenza virus. The discovery of broadly neutralising antibodies (bnAbs) against influenza has opened the possibility of passive immunisation, which could provide protection against multiple influenza strains. Passive immunisation by parenteral administration of purified antibody is challenging, hindered by high antibody production costs and the short half-life of antibody in the circulation leading to relatively transient protection; however the use of viral vectors to deliver bnAbs can begin to address these limitations. Studies presented in this thesis investigated the feasibility of a novel, lung-targeting lentiviral vector pseudotyped with the fusion (F) and haemagglutinin-neuraminidase (HN) coat proteins from Sendai virus (rSIV.F/HN) as a gene transfer agent for bnAb expression. Recombinant SIV.F/HN vector expressing a secreted reporter protein Gaussia luciferase showed expression in the mouse lung lumen 1 month after lung administration. A single dose of rSIV.F/HN encoding novel anti-influenza bnAb (T1-3B) in a single Open Reading Frame directed expression of T1-3B into the lung lumen and systemic circulation, and conferred partial protection against lethal influenza challenge. Intramuscular (IM) delivery of a recombinant adeno-associated virus vector (rAAV2/8), previously reported to be effective against influenza challenge in mice, directed levels of T1-3B that conferred complete protection against influenza challenge. Daily repeat administrations of rSIV.F/HN did not improve protection against influenza challenge, but the ability of this vector to be repeatedly administered without loss of efficacy may be an advantage in potential clinical applications. Engineering of the bnAb, into the IgA1 backbone greatly enhanced the potency of several bnAbs and might improve influenza protection mediated by rSIV.F/HN. In conclusion, prophylaxis provided by gene transfer during an influenza pandemic might be feasible, providing long-lasting, more cost-effective and time-responsive protection than traditional vaccines or parenteral administration of therapeutic antibody.